Response to the work of Charles Baudelaire in the literary criticism and chronicles of Rubén Darío: a spanish perspective - Hambrook, Glyn (Tropelías: Review of Literary Theory and Comparative Literature, 1995)
Rubén DarÍo's infIuence on Spanish "modernismo" and his extensive knowledge of French literature are longstanding commonplaces of literary history. It might therefore be supposed that Darío was in a position to be an infIuential agent of diffusion for the French literary sources in which the "modernistas" sought inspiration. Study of allusions to the work of Charles Baudelaire in the Nicaraguan's literary criticism and chronicles, however, reveals a significantly different picture. For Darío, the self-styled priest of the religion of Art and champion of a pseudo-Christian idealism, Baudelaire was never more than the devil-worshipping poet of vice and spiritual anguish reviled by opponents of the "new literature".Darío's critical response to Baudelaire shows little critical sophistication or originality, yet the esteem in which he was held by the writers of Spain's Fin-de-Siècle does not appear to have prevented them, or at least some of them, from undertaking more penetrating and enlightened readings of the work of the poet of Les Fleurs du Mal.
Keywords: Rubén Darío; Charles Baudelaire